A role for 9-lipoxygenases in maize defense against insect herbivory. (2nd January 2018) - Woldemariam, Melkamu G.; Ahern, Kevin; Jander, Georg; Tzin, Vered
ABSTRACT: Feeding by Spodoptera exigua (beet armyworm) larvae on Zea mays (maize) induces expression of 9-lipoxygenases to a greater extent than 13-lipoxygenases. Whereas 13-lipoxygenases have an established role in the synthesis of jasmonates that serve as defense signaling molecules in many plant species, relatively little is known about the role of 9-lipoxygenases in herbivore defense. Phylogenetic analysis of lipoxygenases from maize inbred lines B73 and W22 shows that, although most Lox genes are present in both lines, Lox12, a 9-lipoxygenase that has been implicated in fungal defense, is truncated and unlikely to encode a functional protein in W22. Two independent Mutator transposon insertions in another 9-lipoxygenase, Lox4, caused improved S. exigua growth on the mutant lines relative to wildtype W22. This observation suggests a function in herbivore defense for metabolic products downstream of maize Lox4, either through direct toxicity or a perhaps an as yet unknown signaling function.